2023
DOI: 10.1037/dhe0000353
|View full text |Cite
|
Sign up to set email alerts
|

Cultural congruity and academic confidence of American Indian graduate students in STEM: Peer interactions, mentor cultural support, and university environment fit.

Abstract: This quantitative study aimed to understand processes germane to Indigenous graduate students' transcultural socialization in Science, Engineering, Technology, and Math fields (STEM). We theorized that transculturation and "wayfinding" are complementary socialization processes to promote healthy socialization of Indigenous graduate students in STEM. We hypothesized that socialization components including peer interactions, mentor's cultural support, and university environment fit would facilitate academic conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…A notable exception is a recent study of American Indian STEM graduate students (Brazill et al. 2021 ), which showed that mentors’ cultural support was associated with increases in the students’ academic self-efficacy. Kirkness, who identifies as First Nation Cree of Manitoba, and Barnhardt, an advocate for Native Alaskan education, wrote about how Native students benefit from academic institutions that convey respect, relevance, reciprocity, and responsibility (Kirkness and Barnhardt 1991 ).…”
Section: Integrating Into Stem Professional Communitymentioning
confidence: 98%
“…A notable exception is a recent study of American Indian STEM graduate students (Brazill et al. 2021 ), which showed that mentors’ cultural support was associated with increases in the students’ academic self-efficacy. Kirkness, who identifies as First Nation Cree of Manitoba, and Barnhardt, an advocate for Native Alaskan education, wrote about how Native students benefit from academic institutions that convey respect, relevance, reciprocity, and responsibility (Kirkness and Barnhardt 1991 ).…”
Section: Integrating Into Stem Professional Communitymentioning
confidence: 98%
“…To address this gap, Johnson et al (2017) recommended that future research explore empirically how students' multiple identities shape their doctoral socialization journey and how they become experts in their profession (Gardner & Doore, 2020;Gardner & Mendoza, 2010). Therefore, for the purpose of this article, I define cross-cultural socialization as a process whereby students embrace their multiple identities throughout their graduate studies and accrue benefits that help them more fully realize the strengths and potential of their experiences and interactions with peers, faculty/mentors, institutions, and places (Brazill & Munday, 2022;Brazill et al, 2021). This definition of cross-cultural socialization is drawn from scholarly work on multiple identities and a strength-based perspective in response to the limitations of research from a deficit lens, which was problematic.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Academic expectations and consistent communications of such policies to students may help them self-regulate to determine whether the amount of seat time lost would help or hinder their well-being accordingly. [19][20][21] Financial Security Poverty and lack of financial capital are barriers that directly impact the potential for AI/AN students to succeed in school. 18,20 Currently, 66% of the AI/AN nursing students in the CO-OP are economically and educationally disadvantaged, as defined by the Department of Education.…”
Section: Sense Of Placementioning
confidence: 99%
“…[15][16][17][18]22 Access to social activities on campus supportive of cultural identity improves retention rates of AI/AN students. [16][17][18][19][20][21]23 Cultural connections help students adapt to the academic environment and promote engagement and institutional commitment. The CON MSU also strategically gathers CO-OP AI/AN alumni to build students' professional networks early and over time.…”
Section: Social Connectionmentioning
confidence: 99%